Knowledge and Adjustment of Wives with Andropausal Husbands in the Federal Capital Territory, Abuja Nigeria: Implications for Guidance and Counselling - Okolo, Michael Monday (Researchparks Publishing, 2022)
This study investigated the wives’ knowledge about andropause and adjustment mechanism towards andropausal husbands in the Federal Capital Territory, Abuja. The study had six objectives, six research questions and four null hypotheses which guided the study. The research design was a survey and a total of 300 wives whose husbands had started experience andropause were involved in the study. the subjects were selected with the use of purposive sampling method. The instrument used to collect the data was researcher designed questionnaire entitle: ‘Knowledge and Adjustment Towards Andropause Questionnaire (KATAQ). The demographic data and research questions were analyzed using simple percentage and means scores. While hypotheses 1 and 2 were tested using t-test and hypotheses 3 and 4 were tested using One-Way ANOVA, All the hypotheses were tested at 0.05 level of significance. The findings showed that, wives had poor knowledge about andropause. Respondents were relatively well adjusted to andropausal husbands, especially wives with tertiary education and longer length of marriage. Results from the tested hypotheses revealed that, level of education had nothing to do with the knowledge of andropause but the adjustment. It is recommended that, wives should develop interest in materials that can broaden their knowledge about andropause because this could lead to a more positive adjustment towards andropausal husbands. This study therefore recommended the need for pre-andropausal counselling for all wives.